The Relationship of Parental Socioeconomic Status with Children's Dental Caries Incidence - Sovira, Gita Dwi Jiwanda; Nismal, Harfindo; Nila, Kasuma; Fitri, Haria; Najla, Qaireenisa (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Dental caries is a multifactorial disease characterized by the destruction of the hard tissues of the teeth. Various age groups can experience dental caries and are more vulnerable in children, especially in elementary school. One of the factors that influence the occurrence of dental caries is the socioeconomic status of parents. Parents' socioeconomic status can be measured by education, occupation, and income. Several studies have shown that dental caries is more common in people with low socioeconomic status. Objectives: This study aimed to determine the relationship between parents' socioeconomic status and dental caries in children aged 11-12 years at SDN 03 Pakan Kurai Bukittinggi. Material and Methods: This study used a cross-sectional design. The number of research samples was 56 children. The sample selection used the Simple Random Sampling method. The instrument used was a questionnaire to measure the parent's socioeconomic status and the dental caries assessment based on the DMF-T/def-t index. Data analysis used a Chi-Square statistical test with p0.05. Results: The results showed that the prevalence of dental caries in children was 83.9%, the DMF-T+def-t index was 2.46, and the socioeconomic status of the respondents' parents was primarily low. The results of statistical analysis between parents' socioeconomic status and children's dental caries obtained p value = 0.000. Conclusion: There was a relationship between parents' socioeconomic status and dental caries in children aged 11-12 at SDN 03 Pakan Kurai Bukittinggi